Oral Medicine: Defining an Emerging Specialty in the United States. Issue 4 (1st July 2012) - Sollecito, Thomas P.; Rogers, Helen; Prescott‐Clements, Linda; Felix, David H.; Kerr, A. Ross; Wray, David; Shirlaw, Penelope; Brennan, Michael T.; Greenberg, Martin S.; Stoopler, Eric T.
Abstract : Oral medicine is a specialized area of study within the scope of dental medicine. This discipline is often viewed as the crossroads between medicine and dentistry and has become integral in both pre‐and postdoctoral dental education. Oral medicine is recognized as a dental specialty throughout most of the world and currently represents an emerging specialty in the United States. Historically, oral medicine has been loosely defined in the United States without a clear consensus definition. Recent published studies regarding international oral medicine postdoctoral programs and clinical practice have helped to provide more specific information regarding oral medicine from many perspectives. This article will review the literature relevant to defining oral medicine in the United States and present a new definition of this important discipline based on recent studies.